Self‐reported work activities, eye, nose, and throat symptoms, and respiratory health outcomes among an industrial hog operation worker cohort, North Carolina, USA. Issue 5 (22nd February 2021) - Coffman, Vanessa R.; Hall, Devon J.; Pisanic, Nora; Love, David C.; Nadimpalli, Maya; McCormack, Meredith; Diener‐West, Marie; Davis, Meghan F.; Heaney, Christopher D.
Abstract: Introduction: Respiratory disease among industrial hog operation (IHO) workers is well documented; however, it remains unclear whether specific work activities are more harmful and if personal protective equipment (PPE), as used by workers, can reduce adverse health outcomes. Methods: IHO workers ( n = 103) completed baseline and up to eight bi‐weekly study visits. Workers reported typical (baseline) and transient (bi‐weekly) work activities, PPE use, and physical health symptoms. Baseline and longitudinal associations were assessed using generalized logistic and fixed‐effects logistic regression models, respectively. Results: At baseline, reports of ever versus never drawing pig blood, applying pesticides, and increasing years worked at any IHO were positively associated with reports of eye, nose, and/or throat irritation. Over time, transient exposures, associated with dustiness in barns, cleaning of barns, and pig contact were associated with increased odds of sneezing, headache, and eye or nose irritation, particularly in the highest categories of exposure. When PPE was used, workers had lower odds of symptoms interfering with sleep (odds ratio [OR]: 0.1; 95% confidence interval [CI]: 0.01–0.8), and eye or nose irritation (OR: 0.1; 95% CI: 0.02–0.9). Similarly, when they washed their hands eight times or more per shift (median frequency) versus less frequently, the odds of any respiratory symptom were reduced (OR: 0.3; 95% CI: 0.1–0.8). Conclusions: In this healthy volunteer worker population, increasingly unfavorable IHO activities were associated with self‐reported eye, nose, throat, and respiratory health symptoms. Strong protective associations were seen between PPE use and handwashing and the odds of symptoms, warranting further investigation.